If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x(x + 8) = 0 Reorder the terms: 9x(8 + x) = 0 (8 * 9x + x * 9x) = 0 (72x + 9x2) = 0 Solving 72x + 9x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '9x'. 9x(8 + x) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Solution
x = {0, -8}
| 100-100)/(100-100)=2 | | -4w^2-5w=0 | | 5x+15=2x-6 | | 5x+6y=-40 | | 4f-2f=6 | | 2x/3=-5 | | 20x^5+8x^3+28x^2=0 | | 5*x^4-2*x-2=0 | | x+136=x+66 | | F(x)=4x^3-12x^2+16 | | Z-12=6 | | 6x+29-4=7 | | F(x)=4x^3-12x^3+16 | | wd-e=6q | | Cos(3*x)+sin(5*x)=0 | | (-7/3x^6)(12x^3) | | f(x)=3x^2+7x-20 | | 3x^3-4x+3=0 | | (7/x^2-36)-(1/x-6) | | (5x-2)(9-y)=64 | | 19+9=33 | | 12n-9+62-3n+162+2=1230 | | 5x(3x-1)=x-4 | | 13x-7=6x+42 | | -5b-4+5-7b= | | 0.75e^0.75/1! | | 7+1+3=20 | | 2+5+4=35 | | 8x=16+16x | | 2sen(x)+2cos(x)=0 | | 15+7=4 | | 10+9=1 |